Genetic Clearness Novel Strategy of Group I Bacillus Species Isolated from Fermented Food and Beverages by Using Fibrinolytic Enzyme Gene Encoding a Serine-Like Enzyme. (20th May 2019) - Kaya-Ongoto, Moïse Doria; Kayath, Christian Aimé; Nguimbi, Etienne; Lebonguy, Aimé Augustin; Nzaou, Stech Anomène Eckzechel; Elenga Wilson, Paola Sandra; Ahombo, Gabriel
Abstract : Fibrinolytic enzyme gene ( fibE ) is widely conserved among Bacillus spp. belonging to group I species. This is encoding a serine-like enzyme (FibE) secreted in extracellular medium. This present work aims to assess the molecular usefulness of this novel conserved housekeeping gene among group I Bacillus spp. to identify and discriminate some related strains in traditional fermented food and beverages in Republic of Congo. First of all 155 isolates have been screened for enzymatic activities using caseinolytic assays. PCR techniques and nested PCR method using specific primers and correlated with 16S RNA sequencing were used. Blotting techniques have been performed for deep comparison with molecular methods. As a result B. amyloliquefaciens (1), B. licheniformis (1), B. subtilis (1), B. pumilus (3), B. altitudinis (2), B. atrophaeus (1), and B. safensis (3) have been specifically identified among 155 isolates found in fermented food and beverages. Genetic analysis and overexpression of glutathione S-transferases (GSTs) fused to mature protein of FibE in Escherichia coli BL21 and TOP10 showed 2-fold higher enzymatic activities by comparison with FibE wild type one. Immunodetection should be associated but this does not clearly discriminate Bacillus belonging to group I.